Palinología de la formación Andapaico (Cisuraliano-Guadalupiano), Precordillera Central Sanjuanina (Argentina): Consideraciones bioestratigráficas regionales - Balarino, María Lucía (2012)
Presented here is a palynological study of samples from the upper part of the Andapaico Formation, Precordillera of San Juan, Argentina. The samples are located just above the eolian facies and have been referred to the Lueckisporites-Weylandites Biozone (LW), probably the basal part, based on comparison with other palynofloras described for the Central-West basins of Argentina. The association is early Cisuralian-middle Guadalupian in age. In addition, 40 species are proposed to be included as new elements unique to the LW Biozone. Comparisons with coeval palynofloras of the Chacoparaná (Argentina), Paraná, and Amazonas (Brazil) biozones were made, showing a high degree of correspondence with the Striatites, Lueckisporites costabilis-Vittatina virkkiae and Vittatina costabilis biozones respectively. According to the botanical affinities of the elements identified in the association, it is possible to infer that they represent a mesophilic flora, with a low participation of hygro-hydrophilic elements, reflecting the absence of wet conditions in areas close to the site of deposition.